Impacts of nitrogen and phosphorus starvation on the physiology of Chlamydomonas reinhardtii - Kamalanathan, Manoj; Pierangelini, Mattia; Shearman, Lauren Ann; Gleadow, Roslyn; Beardall, John (Journal of applied phycology, 2016)
The importance of algae-derived biofuels has been highlighted by the current problems associated with fossil fuels. Considerable past research has shown that limiting nutrients such as nitrogen and phosphorus increases the cellular lipid content in microalgae. However, limiting the supply of nutrients results in decreased biomass, which in turn decreases the overall lipid productivity of cultures. Therefore, nutrient limitation has been a subject of dispute as to whether it will benefit biofuel production on an industrial scale. Our research explores the physiological changes a cell undergoes when exposed to nitrogen and phosphorus limitations, both individually and in combination, and also examines the biotechnological aspects of manipulating N and P in order to increase cellular lipids, by analyzing the lipid production. We show that nitrogen starvation and also nitrogen plus phosphorus starvation combined have a more profound effect on the physiology and macromolecular pools of Chlamydomonas reinhardtii than does phosphorus starvation alone. The photosynthetic performance of C. reinhardtii underwent drastic changes under nitrogen starvation, but remained relatively unaffected under phosphorus starvation. The neutral lipid concentration per cell was at least 2.4-fold higher in all the nutrient-starved groups than the nutrient-replete controls, but the protein level per cell was lower in the nitrogen-starved groups. Overall, nitrogen starvation has a more dramatic effect on the physiology and neutral lipids and protein levels of C. reinhardtii than phosphorus starvation. However, the level of total lipids per volume of culture obtained was similar among nutrient-replete and all of the nutrient-starved groups. We conclude that combined nitrogen and phosphorus starvation does not likely benefit biofuel production in terms of enhanced lipid or biomass production.